Why Is Poetry More Philosophical Than History? Some Remarks On Aristotle’s Poetics - Domański, Iulius (Peitho. Examina Antiqua, 2010)
Aristotle’s statement that — in terms of philosophy — poetry is superior to history can be understood better, when analysed in the context of the Stagirite’s epistemology, ontology, and eudaimonic ethics. Both poetry and history deal with numerous contingent and chaotic events, but while history is only reconstructive, poetry reworks its matter more thoroughly. History attempts to recount all events and does it in accord with their contingent and chaotic nature, whereas poetry implies certain choices. By doing so, it introduces uniformity and coherence thus providing a different ontic status than the one that reigned originally. Consequently, the cognitive result of poetry can be compared to the beatific value of conceptual knowledge in philosophy.